Factors Affecting Vernacular Architecture in Nosmeh Village (Paveh County) - Mino GharehBaglou; Sonya Silvayeh (مسکن و محیط روستا, 2019)
Vernacular architecture is among the most valuable phenomena, which has manifested cultural, historical, social, religious values and so on by itself. The values inherent to vernacular architecture of each city reflect the thinking of the people from that city. Therefore, the peace and quality of people's life can depend on preserving the same architectural values. Preserving and integrating of vernacular architecture values express the secret of human’s integration with their physical environment, which leads to sustainability in every language and culture. Iranian houses are also considered a direct reflection of traditional culture and spiritual values of life and an institution with a multidimensional function, more than a physical structure, that is influenced by society and social relations, culture, religious belief, economy, life style and environmental conditions. Given that vernacular architecture is the symbol of identity, culture and civilization of any region, it seems that the contemporary building designs should be proportional to the vernacular architecture and cultural characteristics of that region. This architecture has met their requirements and desires by reflecting knowledge, careful consideration of the environment, respect for nature, application of time-based technology and spatial capabilities of people. Vernacular architecture is in harmony with nature and environment, the achievements of which are to maintain the comfort of the inhabitants, and it includes maintaining construction cycle, returning to the environment and reusing sustainable resources and the environment. With the environmental and climatic varieties in Iran, different types of vernacular architectures, with identity features, have been formed in this land, and understanding them can be helpful in accurate design and construction of spaces without any defects as is useful in identifying Iranian architecture. On the other hand, new constructions have brought changes in the previous trend of villages, which has created uninhabited, disharmonious and unorganized villages. In this regard, it is important to recognize the factors influencing the formation of rural housing shape and structure. The research questions are, (a) What are the factor(s) influencing vernacular architecture of villages? (b) Which factor(s) has the greatest influence on space in the vernacular architecture of Nosmeh village in the Shamshir rural district? In order to answer the research questions, in the theoretical phase, a framework was presented with the qualitative approach, desk research and using the analytical-descriptive design. In the practical phase, using field studies, preparing a questionnaire and interviewing with local people, the theoretical framework was evaluated using statistical tests in relation to vernacular housing of western Iran. Finally, the findings were analyzed and surveyed using logical reasoning in relation to the theoretical framework proposed in this research and it would be specified that which factor(s) have the greatest impact on space formation. The results of the research indicated that the index of physical construction principles with the maximum average (4.27) was ranked first and geographic location with the minimum average (3.67) was ranked last. In general, four main factors, in other words, physical construction principles, i.e. welfare, beliefs, opinions and geographic location had favorable conditions in the order of priority in terms of effecting the construction.